About Andrés González de Barcia’s library, Royal Councilor of Philip V - Asensio Muñoz, Elena; de los Reyes Gómez, Fermín (Revista General de Información y Documentación, 2018)
One of the most important Spanish libraries of the late seventeenth and early eighteenth centuries was the one gathered by the intellectual and royal counselor Andrés González de Barcia. However, it has not been studied until now. In the present work the documentary sources of the period are presented, which help us to know this particular library, the books that were part of it are studied, taking into account the different marks found in them, especially those that are preserved in the National Library Of Spain, and the collection is analyzed from the quantitative and qualitative point of view.
Keywords: Spanish private libraries; Andrés González de Barcia; Bibliophilia.